Growth and longevity of the freshwater prawn Macrobrachium brasiliense (Decapoda: Palaemonidae) - Nogueira, Caio S. [UNESP]; Porto, Ana Carolina F.; Barros-Alves, Samara P.; Jacobucci, Giuliano B.; Almeida, Ariádine C. (Universidad Nacional Autonoma de Mexico, 2022)
Growth and longevity parameters of males and females of Macrobrachium brasiliense were analyzed. Sampling was carried out monthly from July 2012 to June 2013 in Triângulo Mineiro region, Minas Gerais, Brazil. A total of 199 adult prawns (97 males and 102 females) were analyzed and measured according to the carapace length (CL, mm). Males (9.64 ± 4.17 mm, CL) were larger than females (7.7 ± 3.39 mm, CL). CL growth curves by the von Bertalanffy model are described by the equations CL = 21.0 [1 - e -0.00446 (t)] for males and CL = 20.0 [1 - e -0.00454 (t)] for females. Comparison of the growth curves by performing the F-type test, showed that there was no difference between the growth coefficients (K) of males and females (GL22; F3.16 = 2.476; p = 0.088). Longevity was estimated as 2.83 years for males and 2.78 years for females. In general, the observed longevity is similar to that of other Macrobrachium species.
Crecimiento y longevidad del camarón de agua dulce Macrobrachium brasiliense (Decapoda: Palaemonidae)
Keywords: Caridea; Life strategies; Minas Gerais; von Bertalanffy